KARAKTER MANUSIA DALAM PERSPEKTIF AL-QUR’AN SURAT LUKMAN - Syafi'i, Ahmad Helwani; Syaoki, Muhammad (Universitas Islam Negeri Mataram, 2018)
The character education is the part is very important in human life in order to form of private men to form personal morality in the social life, hence is needed step in business the search for values and the concept of character education based it Alquran that is a source of the truth in excellence. This study aims to to uncover the concept of character education in a lukman with a focus research which includes: 1) a human character in the Alquran letter Lukman; 2) the value of a character in alquran a letter Lukman, 3) the process planting the value of a character that is in Alquran a letter of Lukman.Based on the research done it is found that; 1 a) human character in the Alquran a letter Lukman includes: a ) muhsinin, b ) piety, c) concerns high, d) humble, e) arrogant, f ) and they favors; 2.The value of a character in a lukman includes: a) the value faith / call, b) the value birrul waalidain (kind to older people), c) the value thanks, d) wise, e) the value patient; 3. The process of planting the value of a character in a letter lukman.